Phase composition and phase equilibrium diagrams as the Evidence of the Colloidal State of melts - Pankov Vladimir (E3S Web of Conferences, 2023)
One of the most extensively studied silicate systems with complete miscibility in the solid and liquid state – albite (Ab)-anorthite (An) system – has been analyzed in detail. It has been established that the commonly accepted system and interpretation rules for these diagrams do not match their graphic representation. Calculations have proved the colloidal state of the “solid” phase on the solidus. Actual data support the colloidal (liquid) state of the solidus phase below the solidus and eutectic point. Crystallization in multicomponent systems, at least in silicate melts, has been shown to be based on the sol coagulation mechanism. Thus, silicate solid phases, even those of fixed composition, have no particular melting point. They consolidate and melt within a temperature band. The bandwidth is subject to the system composition that predetermines the micelle structure and directly affects coagulation and peptization processes.